Maternal Warning Signs Education During Home Visiting: Results from a Formative Evaluation in Maryland - Jennifer A. Callaghan-Koru; Inaya Wahid; Shari M. Lawson; Kelly M. Bower; Colleen S. Wilburn; Andreea A. Creanga (Mary Ann Liebert, 2022)
Background: Maternal mortality rate reviews have identified the need for improved patient education regarding the warning signs of maternal complications to reduce preventable deaths. Maternal and child home visiting programs have the potential to deliver this education in communities. Aims: This study sought to evaluate the baseline provision of warning signs education among home visiting programs in Maryland and to assess the acceptability of and preferences for warning signs education materials among program staff. Materials and Methods: This sequential exploratory, mixed-methods study included qualitative interviews and focus group discussions followed by a web-based survey of all home visiting programs providing early postpartum visits in Maryland. Results: Twenty-five home visiting program staff took part in qualitative data collection, and survey responses were submitted by a manager from 40 of 58 eligible home visiting programs (69% response rate). All survey respondents agreed that home visiting programs should provide warning signs education and more than 80% of programs provided some warning signs education during pregnancy and the postpartum period. Printed pamphlets were provided by 68% of programs for pregnancy complications and 43% for postpartum complications. Only 33% of respondents were satisfied with their existing warnings signs education materials; 98% were interested in new illustrated pamphlets and 88% were interested in education videos. Qualitative participants considered pamphlets with simple designs, limited text, and visuals, as the most accessible for home visiting clients. Conclusions: There are opportunities to strengthen and expand warning signs education in Maryland through home visiting programs using new printed and video education materials.